UNDERSTANDING UNITS AND SHIFTS - Iminova Zarifa; Ahmedov A (Ta'lim innovatsiyasi va integratsiyasi, 2024)
Abstract Translation units and shifts are fundamental concepts in translation studies, focusing on how elements of a source language are transformed into a target language. These concepts help in understanding the strategies and methodologies used to achieve accurate and meaningful translations